Evaluation of LLLT Along With Minimally Invasive Flaps in Regeneration of Periodontal Intrabony Defects: A Randomized Controlled Clinical Trial: Evaluation of LLLT in periodontal bone defects - PSG, Prakash; Sanjeev, Kavitha; Subramanian, Sangeetha; Thanigaimalai, Abirami; Appukuttan, Devapriya (Journal of Lasers in Medical Sciences, 2025)
Introduction: The current study aims at evaluating the effectiveness of low level laser therapy (LLLT) in intra-bony defect regeneration by comparing the clinical parameters between periodontitis patients with intra-bony defects treated with simplified papilla preservation flap (SPPF) alone and SPPF with the adjunctive use of LLLT. Methods: The current study is a randomized controlled clinical trial involving 64 patients/sites, 32 sites treated with SPPF – control group and 32 sites treated with SPPF and adjunctive use of LLLT (SPPF+LLLT) – test group. Clinical parameters such as probing pocket depth (PPD), clinical attachment level (CAL), position of gingival margin (PGM), radiographic intra-bony defect depth (R-IBD), full mouth plaque score (FMPS), and full mouth bleeding score (FMBS) were evaluated at baseline, 6 months, and one year post-surgery. Radiographic defect depths were assessed at baseline and one year post-surgery. The results were statistically analyzed. Results: There was a statistically significant reduction in the PPD, CAL, PGM, and radiographic defect depth in the test group at the 6 months and one year post-surgery when compared with the control group (P<0.05). In addition, the total number of sites with PPD more than 4 mm was reduced significantly in the test group when compared to the control group at 6 months and one year. Conclusion: The current study reports a significant improvement in PPD and radiographic intrabony defect fill in periodontitis patients treated with adjunctive LLLT supplementing SPPF. The article evaluates the adjunctive usage of LLLT in periodontal regeneration. The results reiterate the synergistic role of LLLT with periodontal surgical therapy for accelerated regenerative outcomes.